Low‐Temperature Tolerance and Critical Thermal Minimum of the Invasive Oriental Weatherfish Misgurnus anguillicaudatus in Idaho, USA. Issue 1 (11th December 2013) - Urquhart, Alexander N.; Koetsier, Peter
Abstract: The Oriental Weatherfish Misgurnus anguillicaudatus is invasive to many countries around the world, but very little is known about the life history or environmental tolerances of this cryptic fish. As part of a larger study of its life history, we conducted an experiment designed to determine the critical thermal minimum (CTmin) of Oriental Weatherfish collected from water bodies near Boise, Idaho, USA. In each of three experimental trials, 16 fish were placed into individual tanks in an environmental chamber where over the course of 20 d the ambient air temperature was lowered to 0°C. Air temperature was then held at 0°C for 102–134 h. Individual tank temperatures decreased over the course of each trial such that fish were exposed to temperatures ranging from 20°C to −3.64°C. Tank temperatures reaching below the ambient air temperature set‐point were attributed to cold air currents within the environmental chamber. Six of 48 fish died due to temperature‐related factors. Thirty‐eight of the remaining 42 fish survived exposure below the freezing point of freshwater, and 2 fish survived full enclosure in ice with direct contact between skin and ice. In the absence of an observed lethal temperature at which 50% of fish died (LT50), we used logistic regression and observational data to extrapolate a CTmin of −1.8°C. The ability of Oriental Weatherfish to survive at subfreezing temperatures and being embedded in ice indicates a physiological adaptation to cold that may include systemic antifreeze proteins. Tolerance for low temperature and resistance to freezing add to a growing list of characteristics that make the Oriental Weatherfish a highly successful invasive species.